Kinerja Antar Protokol EIGRP, IS-IS, Dan OSPF Dengan Metode Route Redistribution Menggunakan GNS3 - Bagus Prasetya; Primantara Hari Trisnawan; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
There are many routing protocols used in the current network topology. EIGRP, IS-IS and OSPF are examples of routing protocols in a network topology. each of these routing protocols has different algorithm to communicate and also has different ways of working algorithms. Therefore, additional methods such as route redistribute are given so that different protocols can communicate in a topology. In this research, an analysis related to the route redistribute method to find which routing protocol has the best performance in the same network topology. This study uses the Graphical Network Simulator 3 or (GNS3) and uses a hierarchical topology. The scenario is to send an ICMP PING packet from source to destination to observe the round-trip time and convergence time. The results showed that each routing protocol can be run by the route redistribute method. The IS-IS protocol has a round-trip time of 531.4 milliseconds and a convergence time of 158.2 seconds that makes time is the lowest time compared to other protocols and proves that the ISIS protocol is able to work well on the route redistribute method.